Plasma catecholamine excretion in elite freeskiers at a world tour contest - Guschelbauer, R.; Tschan H.; Vidotto C.; Mayr M.; Bachl, N. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Extreme sports, including big mountain and freeskiing are rapidly increasing in popularity. Because of the extremely steep slopes, and dangerous off-piste terrain, single mistakes at the wrong moment are associated with the risk for injuries and even have led to the deaths of some extreme skiers. However, high risk athletes seem to enjoy engaging in stressful conditions that produce a broad spectrum of hormones that cause this psychophysical stress response. The purpose of this study was to characterize the extent of changes of adrenaline and noradrenaline by comparing pre- and post-race plasma concentrations of these catecholamines to quantify the combined psycho-emotional and physical stress response in extreme skiers.